RANCANG BANGUN MONITORING GAS EMISI CO2 DAN KEBAKARAN PADA LINGKUNGAN LAHAN - Surna, Wapa Ahmad; Paramytha, Nina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Oil palm plantations in Indonesia have reached 14,326,350, which is already a large oil palm plantation. However, because there are too many oil palm plantations and they are no longer monitored from the field, therefore there are often fires and CO2 emissions during the dry season in oil palm plantations which spread very quickly to other oil palm plantations and are very detrimental to owners and dangerous for oil palm plantation workers. Therefore, a tool is needed to monitor CO2 emissions and fires in oil palm plantations using LoRa which is connected to an application on a cellphone so that it is easy to monitor if a fire occurs, and for measuring the voltage, the tool used is a battery with a measurement of 8.58 Volt, NodeMCU 3.34 Volt, LoRa 3.28Volt, MQ-02 5Volt, KY-096 5Volr.Key Words: Solar Power, Electrical Energy, Monitoring, ESP 32